Association between miR-365 polymorphism and ischemic stroke in a Chinese population - Weng, Yin-Hua; Yu, Wen-Tao; Luo, Yan-Ping; Liu, Chao; Gu, Xi-Xi; Chen, Huo-Ying; Liu, Hong-Bo (Frontiers in Neurology, 2023)
Background Ischemic stroke (IS) represents a major cause of morbidity and mortality across the globe. The aberrant expression of miR-365 has been found to be implicated in a wide array of human diseases, including atherosclerosis and cancer. Studies on single-nucleotide polymorphisms (SNPs) in miRNA genes can help gain insight into the susceptibility to the condition. This study aimed to examine the relationship between miR-365 SNPs and the risk of IS. Methods The study recruited 215 IS patients and 220 controls. The SNPscans genotyping was employed to genotype three polymorphic loci (rs121224, rs30230, and rs178553) of miR-365. The relative expression of miR-365 in peripheral blood mononuclear cells of the patients and controls was determined by using real-time quantitative PCR. Results The miR-365 rs30230 polymorphism exhibited a significant association with the risk of developing IS (TC vs. CC: adjusted OR = 0.55, 95% CI: 0.33-0.92, P = 0.022; TT vs. CC: adjusted OR = 0.34, 95% CI: 0.14–0.85, P = 0.021; TC +TT vs. CC: adjusted OR = 0.51, 95% CI: 0.31–0.83, P = 0.007; T vs. C: adjusted OR = 0.57, 95% CI: 0.39–0.83, P = 0.004). Haplotype analysis revealed that the C-T-G haplotype was associated with a decreased risk of IS (OR = 0.68, 95% CI: 0.46–1.00, P = 0.047). Furthermore, miR-365 expression was significantly higher in IS patients than in controls (P < 0.001). Interestingly, patients with rs30230 TC or TT genotypes had lower miR-365 levels compared to their counterparts with CC genotypes (P < 0.001). Conclusions The miR-365 rs30230 polymorphism might bear an association with IS susceptibility in the Chinese population, and the rs30230 TC/TT genotype might be a protective factor against IS.